A multi-method approach for groundwater resource assessment in coastal carbonate (karst) aquifers: the case study of Sierra Almijara (southern Spain) - Andreo-Navarro, Bartolomé; Barberá-Fornell, Juan Antonio; Mudarra-Martínez, Matías; Marín-Guerrero, Ana Isabel; García-Orellana, Jordi; Rodellas, V; Vadillo-Pérez, Iñaki (Springer Nature, 2017)
Understanding the transference of water resources within hydrogeological systems, particularly in coastal aquifers, in which groundwater discharge may occur through multiple pathways (through springs, into rivers and streams, towards the sea, etc.), is crucial for sustainable groundwater use. This research aims to demonstrate the usefulness of the application of conventional recharge assessment methods coupled to isotopic techniques for accurately quantifying the hydrogeological balance and submarine groundwater discharge (SGD) from coastal carbonate aquifers. Sierra Almijara (Southern Spain), a carbonate aquifer formed of Triassic marbles, is considered as representative of Mediterranean coastal karst formations. The use of a multi-method approach has permitted the computation of a wide range of groundwater infiltration rates (17–60%) by means of direct application of hydrometeorological methods (Thornthwaite and Kessler) and spatially distributed information (modified APLIS method). A spatially weighted recharge rate of 42% results from the most coherent information on physiographic and hydrogeological characteristics of the studied system. Natural aquifer discharge and groundwater abstraction have been volumetrically quantified, based on flow and water-level data, while the relevance of SGD was estimated from the spatial analysis of salinity, 222Rn and the short-lived radium isotope 224Ra in coastal seawater. The total mean aquifer discharge (44.9–45.9 hm3 year−1) is in agreement with the average recharged groundwater (44.7 hm3 year−1), given that the system is volumetrically equilibrated during the study period. Besides the groundwater resources assessment, the methodological aspects of this research may be interesting for groundwater management and protection strategies in coastal areas, particularly karst environments.
Una investigación multi-método para la evaluación de recursos de agua subterránea en acuíferos kársticos costeros: el caso de estudio de Sierra Almijara (sur de España)
Keywords: Hidrología kárstica; Aguas subterráneas; Acuíferos; Carbonate rocks; Coastal aquifers; Groundwater resources; Water budget; Spain